Asia bond monitor – September 2023 (Asia Bond Monitor)
Covering the Association of Southeast Asian Nations (ASEAN), the People's Republic of China, Hong Kong, China, and the Republic of Korea, the report notes that positive investment sentiment supported a narrowing of risk premiums, a rally in equity markets, and net foreign portfolio inflows. However, interest rates in the region remained elevated, partly due to a rise in bond yields in major advanced economies. Higher borrowing costs have contributed to debt stress and bond defaults in some markets in the region over the past few months.